2020
DOI: 10.1101/2020.03.19.999318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of ACE2 N-terminal fragments binding to SARS-CoV-2 Spike RBD

Abstract: 28Coronavirus disease 19 is an emerging global health crisis. With over 200,000 29 confirmed cases to date, this pandemic continues to expand, spurring research to discover 30 vaccines and therapies. SARS-CoV-2 is the novel coronavirus responsible for this disease. It 31 initiates entry into human cells by binding to angiotensin-converting enzyme 2 (ACE2) via the 32 receptor binding domain (RBD) of its spike protein (S). Disrupting the SARS-CoV-2-RBD binding 33 to ACE2 with designer drugs has the potential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
191
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(204 citation statements)
references
References 22 publications
8
191
3
2
Order By: Relevance
“…[5][6][7] Owing to the crucial role of the SARS-CoV-2 RBD, numerous vaccine and drug candidates have been proposed to target the RBD to inhibit the RBD-ACE2 binding. [8][9][10] However, more research is beginning to show that mutations distal from the RBD (non-RBD mutations) of SARS-CoV-2 also influence its transmissibility. For instance, Walls et al 2 found that by mutating the T678NSPRRAR685 residues, which are distributed around 10 nm from the SARS-CoV-2 RBD, to a variant with T678--IL--R685, the transduction efficiency decreased in human ACE2-expressing Baby Hamster Kidney cells.…”
mentioning
confidence: 99%
“…[5][6][7] Owing to the crucial role of the SARS-CoV-2 RBD, numerous vaccine and drug candidates have been proposed to target the RBD to inhibit the RBD-ACE2 binding. [8][9][10] However, more research is beginning to show that mutations distal from the RBD (non-RBD mutations) of SARS-CoV-2 also influence its transmissibility. For instance, Walls et al 2 found that by mutating the T678NSPRRAR685 residues, which are distributed around 10 nm from the SARS-CoV-2 RBD, to a variant with T678--IL--R685, the transduction efficiency decreased in human ACE2-expressing Baby Hamster Kidney cells.…”
mentioning
confidence: 99%
“…They also generated a hybrid peptide by linking two discontinuous fragments from hACE2 (a.a. 22-44 and 351-357) with a glycine, and this 31-mer exhibited a potent antiviral activity with an IC50 of about 0.1 μM, indicating that this artificial peptide had much stronger binding affinity for SARS-CoV RBD than the peptides composed of residues 22-44 or 22-57. Due to the high similarity of the binding interfaces between SARS-CoV RBD/hACE2 and SARS-CoV-2 RBD/hACE2, we think that this artificial peptide may also bind to SARS-CoV-2 more strongly than the peptide 21-43 tested by Zhang et al 14 , which is similar to the peptide 22-44 from Han et al 16 . Although the natural peptides are promising, it has been argued that the sequence of hACE2 is suboptimal for binding the S protein of SARS-CoV-2 17 .…”
Section: Introductionmentioning
confidence: 58%
“…These positive features make peptides great candidates to serve as therapeutics 12,13 . Recently, Zhang et al 14 reported that the natural 23-mer peptide (a.a. cut from the human ACE2 (hACE2) α1 helix can strongly bind to SARS-CoV-2 RBD with a disassociation constant (Kd) of 47 nM, which was comparable to that of the full-length hACE2 binding to SARS-CoV-2 RBD 15 ; they also showed that a shorter 12-mer peptide (a.a. [27][28][29][30][31][32][33][34][35][36][37][38] from the same helix was not able to bind the virus RBD at all. In an earlier report, Han et al 16 performed a study to identify the critical determinants on hACE2 for SARS-CoV entry, and they found that two natural peptides from hACE2 (a.a. 22-44 and 22-57) exhibited a modest antiviral activity to inhibit the binding of SARS-CoV RBD to hACE2 with IC50 values of about 50 μM and 6 μM, respectively, implying that the peptide composed of residues 22-57 had stronger binding affinity for SARS-CoV RBD.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, HD5 had less of an effect on ACE2-S1 interaction ( Figure 2B), possibly due to a binding site distant from the RBD. Recent studies have discovered some antibodies and peptides with high affinities binding to the spike 32, 35 . These candidates are placed hopes on suppressing 2019-nCoV.…”
Section: Resultsmentioning
confidence: 99%